2010
DOI: 10.1007/s10661-010-1653-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in plant leaves as a biomarker of pollution due to anthropogenic activity

Abstract: The air pollution due to anthropogenic activities seriously affected human life, vegetation, and heritage as well. The vegetation cover in and around the city mitigates the air pollution by acting as a sink for pollution. An attempt was made to evaluate biochemical changes occurred in four selected plant species, namely Azadirachta indica, Mangifera indica, Delonix regia, and Cassia fistula of residential, commercial, and industrial areas of Nagpur city in India. It was observed that the correlated values of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
(25 reference statements)
0
14
4
Order By: Relevance
“…pH signals the occurrence of detoxication process in plant necessary for tolerance (Thawale et al 2011). Terminalia catappa, Mangifera indica, Ficus platyphylla and Polyalthia longifolia leaf extract pH in this study were found to be acidic in nature at the arterial road sites.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…pH signals the occurrence of detoxication process in plant necessary for tolerance (Thawale et al 2011). Terminalia catappa, Mangifera indica, Ficus platyphylla and Polyalthia longifolia leaf extract pH in this study were found to be acidic in nature at the arterial road sites.…”
Section: Discussionmentioning
confidence: 55%
“…Leaf extract pH, relative water content (RWC), total chlorophyll content and ascorbic acid were used to determine (Thawale et al 2011) tolerance and sensitivity of the tree species to vehicular emissions. They were taken as numerical expression to get an observed value indicating Air Pollution Tolerance Index (APTI) as proposed by Singh and Rao (1983).…”
Section: Evaluation Of Tolerance and Sensitivity Of Tree Species To Vmentioning
confidence: 99%
“…The literature has reports of phytotoxicity caused by air pollutants in araça trees and other bioindicator species. Changes in the levels of chlorophylls (including symptoms of chlorosis and necrosis), sugars, proteins and other organic components (Thawale et al, 2011;Rai, 2016) are some physiological effects that may affect biomass production and plant growth. Studies on P. cattleianum submitted to the effects of pollutants in Brazil have revealed significant alterations in the antioxidant metabolism and vegetative growth of this plant (Moraes et al, 2002;Alves et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The former may be due to more pollution stress by hindering chlorophyll biosynthesis or various chlorophyll degradation products (fluorescent/non-fluorescent chlorophyll catabolite) or stress induced chlorosis, pheophytinisation, reverse bleaching, etc. (Thawale ., 2011). Conversely, higher chlorophyll content was observed mostly during morning hours which might be due to plants' innate tolerance mechanism against air pollutant-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%